Organic Semiconductor Detector for Large Area Digital Imaging - Shafique, Umar (University of Waterloo, 2014)
Organic semiconductor technology has gained attention in both the sensor and display markets due to its low cost and simple fabrication techniques. The ability to fabricate organic semiconductor devices such as photodetectors and transistors on a flexible, lightweight substrate makes them less fragile and ideal candidates for portable large-area imaging applications. The use of organic semiconductor technology in large-area medical imaging can bring about a new generation of flexible and lightweight indirect X-ray imagers. These imagers are immune to mechanical shock and should be ideal for portable intraoral X-ray radiology. In order to realize these organic flexible imagers and their use in large-area medical imaging, many challenges associated with the device performance and fabrication need to be overcome. Among these challenges, one of the greatest is to improve the dark current performance of the organic semiconductor photodetectors (key for imager performance) with a high-photo to-dark current ratio. Low dark current is needed to improve the sensitivity of the imager, whereas a large photo-to-dark current ratio reduces noise in the extracted image. Numerous techniques have been reported to improve the dark current performance in vertical organic photodetector design; however, lateral photodetectors still lack research attention. This thesis presents a lateral multilayer photodetector design and a simplified technique to improve the dark current performance of lateral organic semiconductor photodetectors. Our technique allows us to apply a large bias voltage while maintaining a low dark current, high photo-to-dark current ratio, and improves detector speed; thus, the overall sensitivity of the detector is improved. We further show the integration of an organic photodetector with an organic backplane readout circuit to form a flexible large-area imager. This imager can be used for large-area digital imaging applications such as in medical radiology.
Keywords: Low Cost Large Area Digital Imaging; Flexible Indirect X-ray Digital Imager; Organic Semiconductor Flat Panel Digital Imager; Digital Imager on Plastic Substrate; Organic Semiconductor Large Area Digital Imager; Organic Semiconductor Photodetector; Lateral Photodetector; Interface Layer; Low Dark Current; Lateral Multilayer Photodetector; Solution Processed; Photodetectors; Electrical and Computer Engineering (Nanotechnology)